A heuristic approach to selecting views for materialization. (13th March 2013) - Roantree, Mark; Liu, Jun
SUMMARY XML data warehouses are becoming more popular as data is harvested from the web or as output from web services. As these warehouses tend to grow significantly over time, various techniques for expediting queries have been developed. One such technique is to materialize some or all of the queries in advance of query processing. These views are then subject to change either when underlying data changes or view definitions themselves are modified by users. The work in this paper focuses on changes to view definitions or view adaptation as it is known. Our approach is to segment the materialized view into fragments to minimize the effect of view changes. One crucial aspect to this approach is how to select the best fragments for materialization. In this paper, we introduce a new approach to selecting fragments based on heuristics derived from costs associated with the view graph. Copyright © 2013 John Wiley & Sons, Ltd.